2004
DOI: 10.1111/j.1741-4520.2004.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fetal DNA from maternal peripheral blood by lectin‐polymerase chain reaction–single strand conformation polymorphism

Abstract: Fetal nucleated cells in maternal peripheral blood are a non-invasive source of fetal DNA for prenatal genetic diagnosis. However, the number of fetal cells present in maternal peripheral blood is very small. Therefore, fetal cell enrichment is generally considered necessary to allow detection and subsequent genetic analysis of the rare fetal cells. In the study presented here, we performed fetal cell separation from maternal blood using galactose-specific lectin to concentrate fetal nucleated red blood cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The combination of the LCM technique with image analysis has the potential to become a leading method for analysis of fetal DNA, because selection of single cells by LCM can be used to provide the whole genome even if the sample only has a small number of erythroblasts. We previously amplified the SRY gene in erythroblasts isolated by MGG staining and manual detection combined with the LCM technique . In the present study, the X and Y chromosomes plus the SRY gene were found in erythroblasts identified by automated image analysis, which detected more cells than manual searching.…”
Section: Discussionmentioning
confidence: 57%
“…The combination of the LCM technique with image analysis has the potential to become a leading method for analysis of fetal DNA, because selection of single cells by LCM can be used to provide the whole genome even if the sample only has a small number of erythroblasts. We previously amplified the SRY gene in erythroblasts isolated by MGG staining and manual detection combined with the LCM technique . In the present study, the X and Y chromosomes plus the SRY gene were found in erythroblasts identified by automated image analysis, which detected more cells than manual searching.…”
Section: Discussionmentioning
confidence: 57%